Treatment of elopement following a latency‐based interview‐informed, synthesized contingency analysis. (24th April 2018) - Jessel, Joshua; Ingvarsson, Einar T.; Metras, Rachel; Whipple, Ruth; Kirk, Hillary; Solsbery, Lauren
Abstract : Using a latency measure during a functional analysis of problem behavior increases the brevity of the assessment period and decreases risks resulting from exposure to contexts intended to evoke problem behavior. In addition, latency‐based functional analyses may be especially suitable for discrete behaviors such as elopement, which require resetting the environment after each instance of the response. We evaluated a comprehensive assessment and treatment package for the elopement of two children diagnosed with autism. We observed short latencies to elopement during the test condition of the analysis and no elopement during the control condition. We then taught the participants multiple forms of functional communication responses of increasing complexity while elopement was blocked. This was followed by the thinning of reinforcement to a terminal goal, creating a treatment package that nearly eliminated elopement and was socially validated by caregivers.